A study of the leaves of Manihot esculenta Crantz (Family Euphorbiaceae) - Loyola, Ruth; Lopez, Maria Bella; Concepcion. Adoracion B. (Quezon City: College of Pharmacy, University of the Philippines, 1979.)
The leaves of the Manihot esculenta Crantz was finely crushed and powdered. The material was added with 95% ethyl alcohol and a simple extraction procedure was done on it. The alcoholic extract was then analyzed by thin layer and column chromatography.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, June 2018.
Keywords: Cassava